Trading hours deregulation in Tasmania and Western Australia: large retailer dominance and changing models of development. (3rd April 2017) - Heino, Brett
ABSTRACT: The transformation of Australian capitalism from the 1970s onwards has exercised a tremendous impact on trading hours legislation. In the shift between an antipodean Fordist and liberal-productivist model of development, the competition principle has assumed central importance, eroding perceived legislative fetters to free competition and more generally spurring a withdrawal of the state from direct economic regulation. Trading hours legislation is a prime example of this reality. Whereas the 1960s was an era of more-or-less regulated and circumscribed trading hours, the movement throughout the 1970s–2000s has been towards progressively looser controls. This is a movement driven by large retailers, who have found themselves wielding immense economic and political power within the fabric of liberal-productivism. Their efforts to squeeze out smaller operators through the continual extension of trading hours also dovetailed with a general effort on the part of the national state to diffuse the competition principle throughout the Australian economy, represented most graphically by the National Competition Policy of the 1990s. Given the historically state-based character of shop hours in Australia, this movement is demonstrated by an analysis of two case-study states, Western Australia and Tasmania.